2015
DOI: 10.1038/nn.3957
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal ensembles sufficient for recovery sleep and the sedative actions of α2 adrenergic agonists

Abstract: Do sedatives engage natural sleep pathways? It is usually assumed that anesthetic-induced sedation and loss-of-righting-reflex (LORR) arise by influencing the same circuitry to lesser or greater extents. For the α2 adrenergic receptor agonist dexmedetomidine, we find that sedation and LORR are in fact distinct states, requiring different brain areas, the preoptic hypothalamic area and locus coeruleus (LC) respectively. Selective knockdown of α2A adrenergic receptors from the LC abolished dexmedetomidine-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
312
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(325 citation statements)
references
References 48 publications
7
312
1
5
Order By: Relevance
“…We have previously suggested that sedatives produce sleep by interacting with the NREM sleep-inducing circuitry, changing activity in the hypothalamic and brainstem circuits that globally govern arousal (Nelson et al, 2002;Lu et al, 2008;Zhang et al, 2015). We show here that this seems to be the case for zolpidem, too.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We have previously suggested that sedatives produce sleep by interacting with the NREM sleep-inducing circuitry, changing activity in the hypothalamic and brainstem circuits that globally govern arousal (Nelson et al, 2002;Lu et al, 2008;Zhang et al, 2015). We show here that this seems to be the case for zolpidem, too.…”
Section: Discussionsupporting
confidence: 68%
“…Natural NREM sleep is hypothesized to start when GABA neurons in the preoptic hypothalamus increase their activity onto, among other targets, the wake-promoting histaminergic neurons in the tuberomammillary nucleus (TMN) of the posterior hypothalamus (Nitz and Siegel, 1996;Sherin et al, 1996Sherin et al, , 1998Zhang et al, 2015). Infusing the GABA A agonist muscimol into this area induces sleep (Lin et al, 1989;Nitz and Siegel, 1996); conversely, injecting GABA A receptor antagonists there decreases the potency of GABAergic anesthetics (Nelson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…9 In another study in vivo, acute knockdown of α 2A -AR expression in the locus coeruleus failed to affect DEX induced sedation. 46 These findings suggest that α 2A -ARs on non-adrenergic neurons mediate their sedative effects. Furthermore, dopamine-β-hydroxylase knockout mice that have no synaptic norepinephrine release show enhanced sensitivity to and delayed emergence from DEX-induced hypnosis compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 95%
“…45 However, more recent studies have implicated effects of α 2 -AR agonists on non-adrenergic neurons in these actions. 9,46,47 Genetically engineered mice that express α 2A -ARs only in noradrenergic terminals show minimal neurological effects of the α 2 -AR agonist medetomidine, including loss of righting reflex and anesthetic-sparing, in contrast to a strong hypnotic effect in wild-type littermates. 9 In another study in vivo, acute knockdown of α 2A -AR expression in the locus coeruleus failed to affect DEX induced sedation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation